“Five on a Dice” Port Placement Allows for Successful Robot-Assisted Left Pneumonectomy - Khan, Najah; Fikfak, Vid; Chan, Edward Y.; Kim, Min P. (The Thoracic and Cardiovascular Surgeon Reports, 2017)
Background Technology has evolved to facilitate pulmonary resection. The latest technological advances in computer-aided surgery (Da Vinci Xi) allow for more control during pulmonary resection.Case Description A 59-year-old woman presented with two primary tumors of the left upper and lower lung. After induction chemotherapy, patient had a “five on a dice” port placement and technique was used to perform successful robot-assisted pneumonectomy. The patient was discharged home on postoperative day 3 without any complications.Conclusions We have found that the “five on a dice” port placement allows for optimal control of the robot stapler and facilitates successful robot-assisted left pneumonectomy.
Keywords: lung cancer treatment; robotics; minimally invasive surgery